(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Investment decisions are always crucial. Lots of financial gains anticipations are included in investment decisions. Investors make different calculation before investing. Yet, the investment decisions are not always based up on financial calculation only. Investors become influenced by other concerns like imitation of peer group, advise of elders etc. Studying such influencing factors is subject matter of behavioural finance. In the present study the researchers have focused upon the behavioural finance theories as a determinant of the investment decisions. Researchers have used different behavioural finance theories to establish constructs. A questionnaire has been developed to test the different aspects of investment decisions. The reliability analysis (Cronbach’s Alpha 0.751) of the questionnaire has been conducted. Further the questionnaire extracted 10 variables. These have been named as Individual Investors’ Investment Decisions, Risk Consideration, Value consideration, Fear of Missing Opportunity, Regret Aversion, Psychological Influence, Cognitive Dissonance, Emotion of Investor, Over Reactive Instinct, Under Reactive Instinct. These variables have been tested for corelation and further multiple corelation coefficient. R value 0.786 suggested the established variable has significant impact on each other.